2025 Brazilian guidelines for the management of neuromyelitis optica spectrum disorder in adults and children. - Apóstolos-Pereira, Samira Luisa Dos; Damasceno, Alfredo; Piccolo, Ana Claudia; Mendes, Maria Fernanda; Brito, Maria Lúcia; Alvarenga, Regina; Costa, Bruna Klein da; Sato, Douglas Kazutochi; Brum, Doralina Guimarães [UNESP]; Mello, Elisa; von Glehn, Felipe; Passos, Giordani; et al. (Thieme, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is a debilitating recurrent inflammatory disease of the central nervous system. Establishing management guidelines is essential to optimize patient care in Brazil.To combine the Delphi and Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approaches to validate evidence-based guideline statements for NMOSD treatment.These guidelines focused on providing recommendations for different scenarios: general management and diagnosis of NMOSD; acute and preventive treatments (including systemic immunosuppressants and anti-B cell, anti-interleukin-6, and anti-complement monoclonal antibodies); and therapeutic approaches in special groups (such as the pediatric population and pregnant women). A literature review based on the Population, Intervention, Comparator, and Outcome (PICO) framework was performed, and studies were evaluated using the GRADE system. An initial questionnaire containing 19 statements was sent to 44 specialists from all regions of Brazil.Three voting rounds were necessary to reach consensus in all statements. After the first voting round, 17 statements reached consensus (level of agreement > 70%). Two statements failed to reach consensus and were, thus, revised. One of them was segmented into three different statements. After the second voting round, three out of the four revised statements reached consensus. Upon further revision, the last statement was again submitted to voting, reaching consensus in this third round. Overall, agreement was achieved on the 21 proposed statements.The primary objective in the management of NMOSD is to mitigate the severity of the attacks and prevent relapses, thereby minimizing the risk of irreversible neurological deficits. The statements in the current guideline offer evidence-based recommendations for such management within the Brazilian context.